Adesão ao tratamento imunossupressor em pacientes submetidos ao transplante de fígado - Angela Aparecida de Lima (2019)
Liver transplantation is a procedure that represents the only possible therapy for patients with end-stageliver diseases. Adherence to immunosuppressive therapy (ISS) is essential for survival of the transplanted organ. Rejection, graft loss, and death in patients have been recorded and frequently associated with non - adherence to immunosuppressive treatment. This study aims to evaluate the prevalence of adherence to immunosuppressive treatment in patients undergoing liver transplantation, and identify the risk factors for this behavior, assessing adherence differences from the postoperative period. A cross-sectional study was proposed with transplanted liver patients with more than one year of transplantation carried out at a university hospital in Belo Horizonte, Minas Gerais. Patients completed the Basel Scale for Adherence to Immunosuppressive Drugs (BAASIS) and sociodemographic questionnaire. A total of 300 liver receptors were included in the study, of which 186 (62%) were male, 158 (52.7%) were 50 years old or older, average age of 55 years, 172 (57.3% %) were married, 222 (74%) had five years or more of transplantation and those who transplanted in a special situation accounted for 21.7% (65). Of this contingent, 61.3% adhered to the immunosuppressive treatment. The risk factor identified in the analysis was having five years or more of transplantation (p = 0.027) and to be single (p = 0.08). The independent protective factors for adhesion to the immunosuppressive regimen were transplantation in a special situation (p = 0.004, OR 0.52, CI = 0.28: 0.97), being married (p = 0.007, OR 0.44, CI 0.24: 0.79) and being separated or divorced (p = 0.001, OR 0.20, CI 0.08: 0.54). Transplantation time of five years or more (p = 0.056, OR 1.76, CI 0.99: 3.13) showed a tendency to the risk of non-adherence. It was concluded that adherence to the immunosuppressive treatment found (61.3%) is within the adhesion range recorded in other studies on the same subject. The risk factors found were being single and having five years or more of transplantation also appeared in other studies. Exclusive discoveries were made in this area as the protective factors for adherence: being married, separated / divorced and having been transplanted in a special situation.